The opacity of the intergalactic medium measured along quasar sightlines at z~6 - Eilers, Anna-Christina (The astrophysical journal, 2018)
We publicly release a new sample of 34 medium resolution quasar spectra at 5.77 ≤ z em ≤ 6.54 observed with the Echellette Spectrograph and Imager on the Keck telescope. This quasar sample represents an ideal laboratory to study the intergalactic medium (IGM) during the end stages of the epoch of reionization, and constrain the timing and morphology of the phase transition. For a subset of 23 of our highest signal-to-noise ratio spectra (S/N > 7, per 10 km s−1 pixel), we present a new measurement of the Lyα forest opacity spanning the redshift range 4.8 ≲ z ≲ 6.3. We carefully eliminate spectral regions that could be causing biases in our measurements due to additional transmitted flux in the proximity zone of the quasars, or extra absorption caused by strong intervening absorption systems along the line of sight. We compare the observed evolution of the IGM opacity with redshift to predictions from a hydrodynamical simulation with uniform ultraviolet background (UVB) radiation, as well as two semi-numerical patchy reionization models, one with a fluctuating UVB and another with a fluctuating temperature field. Our measurements show a steep rise in opacity at z ≳ 5.0 and an increased scatter and thus support the picture of a spatially inhomogeneous reionization process, consistent with previous work. However, we measure significantly higher optical depths at 5.3 ≲ z ≲ 5.7 than previous studies, which reduces the contrast between the highest opacity Gunn-Peterson troughs and the average opacity trend of the IGM, which may relieve some of the previously noted tension between these measurements and reionization models.
Gesehen am 01.09.2020